“Comportamiento agronómico del cultivo de pepino (Cucumis sativus) con diferentes dosis de biol en el cantón La Maná provincia de Cotopaxi.” - Olmedo Zambrano, Pablo Javier (2023)
In the 7 Arcángeles district of La Mána canton, Cotopaxi province, 120 plants of cucumber variety Market More 76 were established for studying the agronomic response of cucumber cultivation (Cucumis sativus) with the different dosages of biol in sector 7 Arcángeles of La Maná canton. The experimental units consisted of 4 treatments and 5 repetitions, the following doses were applied T1A (500ml), T2B (1lit), T3C (1.5lit) and Witness (unapplied). The experimental methodology used was the Design of Complete Blocks at Random with four treatments and five repetitions. In order to meet with the proposed objectives, the following variables were taken into account, plant height in (cm), days to bloom, number of fruits per plant, weight of fruits per plant (kg), fruit length in (cm), fruit diameter in (cm), yield in (kg/par). As described in Table 14 it is important to emphasize that the application of biol was done from the 15 days of its sowing. That is to say that it was applied at 15, 30 and 45 days, in concentrations doses of 5% in 10lit water; 10% in 10lit water and 15% in 10 liters of water from a 20-liter pump. As Zamora (2017), determined that these concentrations are suitable for cucumber cultivation, because it is not very demanding in terms of plant matter in soil decomposition, but due to its short-cycle, it is necessary to provide the required nutrients since the sowing time. Days after the application of biol, a record was kept in the field book where according to the results it is known that the T3C in the yield variable of table 20 was the best treatment; with 7 030 g/par at 45 days. At 60 days the T3C with 8 100 g/par. At 75 days the T3C with 8 130 g/par. Therefore, at 90 days the T3C with 9 050 g/par, is considered the best treatment.